2016
DOI: 10.1038/nmicrobiol.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of the lung microbiome with oral taxa is associated with lung inflammation of a Th17 phenotype

Abstract: Microaspiration is a common phenomenon in healthy subjects, but its frequency is increased in chronic inflammatory airway diseases, and its role in inflammatory and immune phenotypes is unclear. We have previously demonstrated that acellular bronchoalveolar lavage samples from half of the healthy people examined are enriched with oral taxa (here called pneumotypeSPT) and this finding is associated with increased numbers of lymphocytes and neutrophils in bronchoalveolar lavage. Here, we have characterized the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
498
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(527 citation statements)
references
References 59 publications
25
498
2
2
Order By: Relevance
“…In the air space, an alveloar macrophage secretes cytokines, IL-8 and TNF-α, which act locally to stimulate chemotaxis and activate neutrophis. [25] Our research also shows that IL-8 and TNF-α levels were significantly affected at 24 h post injury in the 1:3 fluid resuscitation group compared with those in the 1:1 fluid resuscitation group (Figure 5c, d). Collectively, these findings suggest that fluid resuscitation significantly attenuates lung injury in rabbit.…”
Section: Discussionsupporting
confidence: 67%
“…In the air space, an alveloar macrophage secretes cytokines, IL-8 and TNF-α, which act locally to stimulate chemotaxis and activate neutrophis. [25] Our research also shows that IL-8 and TNF-α levels were significantly affected at 24 h post injury in the 1:3 fluid resuscitation group compared with those in the 1:1 fluid resuscitation group (Figure 5c, d). Collectively, these findings suggest that fluid resuscitation significantly attenuates lung injury in rabbit.…”
Section: Discussionsupporting
confidence: 67%
“…46 Prevotella -high and -low community profiles have been noted in healthy subjects, 14,30 with the Prevotella- high profile being associated with enhanced “subclinical” lung inflammation, that is notable for enhanced expression of inflammatory cytokines and elevated Th-17 lymphocytes. 30,52 However, association studies do not determine the direction of causality and this data would be very consistent with a model where subclinical airway inflammation leads to higher levels of micro-aspirated Prevotella . In support of this model is the observation in cystic fibrosis patients that colonization with P. aeruginosa , a pro-inflammatory bacteria, significantly increased the likelihood that Prevotella will be present.…”
Section: Lung Microbiota and Immunitymentioning
confidence: 63%
“…It is possible that the microbiomes may change depending on the grade of fibrosis and honeycomb change. Previous studies have shown that patients with some respiratory past history have different microbiomes than those of healthy volunteers [27]. Furthermore, antibiotics, antacids, inhaled corticosteroids and nutritious food, which can cause microbial changes, should be considered.…”
Section: Discussionmentioning
confidence: 99%